Additional Considerations When Using the FASB Data Bank of Changing Price Information - Thomas, Lynn R.; Swanson, Edward P. (The Accounting Review, 1986)
[In a recent issue of The Accounting Review, Stone and Bublitz (S&B) [1984] report on the frequency of data collection errors for the 1981 FASB computer tape containing FAS 33 disclosures for 1979 and 1980. This paper extends their work by examining the problems encountered when using a subsequent version of that data base in conjunction with the Compustat and Value Line historical cost data bases. Failure of the data bank user to reconstruct the difference between historical cost and current cost amounts in the supplementary disclosures of a firm's annual report is designated as an error. Errors in income and depreciation expense for a filtered sample of 171 firms are reported for the years 1979 through 1982. An error rate for income in 1981 of 12.9 percent and error rates for depreciation ranging from 23.4 to 39.8 over the four years seem to suggest that manual checking of annual reports is necessary when using these amounts.]